BIOCHEMICAL MARKERS OF LIVER DAMAGE IN RESPIRATORY ALLERGOSES IN CHILDREN (International Journal of Scientific Pediatrics, 2024)
Summary: This review presents the results of scientific work devoted to the study of biochemical markers of liver damage in respiratory allergies. It has been established that with respiratory allergies in children there is an increase in markers of liver damage without morphological changes. Purpose of the study: to study changes in biochemical markers and morphometric parameters of liver damage in respiratory allergies. Objectives of the study: to examine the concentration of liver enzymes: ALT, AST, alkaline phosphatase, gammaglutamine transpeptidase, as well as IL-4, IL-17A and morphometric parameters of the liver in children with respiratory allergies. Materials and methods. The study was conducted at the Department of Allergology and Gastroenterology of the Bukhara Regional Multidisciplinary Medical Center. 60 children aged 4-10 years were examined and divided into 3 subgroups. The first subgroup included 20 children with bronchial asthma, the second - 20 children with respiratory allergies (allergic rhinitis, sinusitis, allergic tracheitis, bronchitis). The control group 3 consisted of 20 healthy children. All children underwent general and biochemical blood tests (ALT, AST, total bilirubin, alkaline phosphatase (ALP), gamma-glutamyl transpeptidase (GGT), IL-4, IL-17A and liver ultrasound. Results and its discussion. The study of liver transaminases in respiratory allergies made it possible to establish an increase in ALT and AST in patients of group 2 to 44.42±5.9 units/l and 56.1±11.9 units/l, against the control - 25.97±4.15 U/L and 22.69±3.0 U/L, respectively (p
Keywords: biochemical markers of the liver; respiratory allergies; cytokines